The Interplay Between Theory of Mind and Social Emotional Functioning in Adolescents With Communication and Language Problems - Smit, Lidy; Knoors, Harry; Hermans, Daan; Verhoeven, Ludo; Vissers, Constance (Frontiers in Psychology, 2019)
Adolescents with developmental language disorders (DLD) and adolescents who are deaf or hard of hearing (D/HH) are at greater risk of social emotional problems. These problems may not only be attributed to communication and language problems but, at least in part, to Theory of Mind (ToM) deficits as well. In this mini-review, an overview is provided of studies on social emotional functioning and ToM performance in adolescents with DLD and D/HH adolescents. A possible interplay between social emotional functioning and Theory of Mind is discussed. There is empirical evidence for social emotional problems and ToM problems in both adolescents with DLD and D/HH. We hypothesized that language deficits as seen in adolescents with DLD and impoverished exposure to language and communication, as seen in adolescents that are D/HH can explain differences in social emotional functioning and ToM performance. The present mini-review provides a possible framework for the relation between ToM and social-emotional functioning in adolescents with communication and language problems which is mediated by their limited linguistic ability or restricted language exposure and gives suggestions for future research.